Global mental shift: political values of the youth of Russia and Europe - I. A. Vetrenko; Yu. P. Bayer; V. A. Vasilyeva (Правоприменение, 2022)
The subject of the article is the political values of the youth of Russia and Europe.The purpose of our study is to identify the political values of the Youth of Russia and Europe and conduct a comparative analysis based on the methodology of comparative analysis. Four hypotheses are tested that suggest the values of young people, regardless of the region or country of residence, are common, despite the differences in forms of government, political culture, living standards and traditions of the respondents.The main research tasks were: 1. Identification of common value orientations of modern youth studying at universities. 2. Determination of the type of cultural mentality (according to the methodology of Russian American sociologist Pitirim Sorokin) of the youth of Russia and European countries included in the sample. 3. Determining the place of politics and the opportunity to participate in policymaking in the system of values of today's youth. 4. Identification of attitudes (loyalty / acceptance / non-acceptance) to modern democratic values, as well as identification of the preferred form of political governance among young people. 5. Determination of the desired type of taxation. 6. Establishing the relationship between political values and quality of life. 7. Determining the understanding of the components of happiness (wellbeing) and the meaning of life of modern youth. 8. Diagnosis of the degree of involvement in politics/apathy of today's youth.The main results, scope of application. Study made it possible to introduce into contemporary science a new term "integral model of values" – an interconnected set of several life values of a person, each of which describes individual components of values, to form a complete and comprehensive idea of the value system of certain social groups. Empirical study made it possible to identify the basic components of the integral model of values of modern youth in Russia and Europe in a comparative aspect. Under the integral model of values, authors mean an interconnected set of several private value models of a person (mentality, basic human and social values, life satisfaction and a subjective feeling of happiness, political views and actions, cultural values, etc.), each of which describes individual components of values, and all together they form a complete and comprehensive idea of the value system of certain social groups. In the structure of the integral model of youth values, authors included: mentality, political values, political mobility and a system of universal values. In accordance with this structure, we present the results of our study.Conclusions. Authors not only managed to identify the already established values and, on the basis of them, draw up an integration model of the values of the youth of Russia and Europe through their comparison, but also to determine the needs of today's youth for certain values.